Learning about Islam and Islamic civilisation through a webquest: perspectives from pupils and their teacher - BinTaleb, Abdulaziz (British Journal of religious education, 2021)
This article describes one of the first webquests that was designed to enhance middle- and secondary-school pupils’ understandings of Islam and Islamic civilisation. It also explores teachers’ and pupils’ perspectives on their experiences of the webquest’s implementation. Pupils actively participated and collaborated in conducting this web-based project by learning basic information about Islam and reflecting on their understanding of the factors that led to the rise and decline of Islamic civilisation. Quantitative and qualitative data were collected through the use of pre- and post-project surveys which were disseminated among pupils, as well as by capturing feedback from the teacher through the medium of an interview. Pupils’ perspectives regarding the use of the webquest were very positive. The findings illustrate that the webquest is suitable for middle-school pupils as a web-based instructional tool for learning about Islam and Islamic civilisation. These findings highlight the potential of this particular webquest to fill a gap regarding the need for appropriate instruction for an important subject.